Efficacy of proinflamatory cytokines in the clinical and radiograpic outcomes of different primary molar pulpotomy agents: a comperative randomised study featuring a novel biomarker for pulpal diagnosis - Aybike Bas; Sera Simsek Derelioglu; Esra Laloglu (BMC, 2024)
Abstract Background While the effect of biomaterials covering the pulp tissue is considered in the success of pulpotomy treatment, the level of pulpal inflammation is still very important for treatment success. The aim of this study was to compare IL-6 and IL-8 levels, known as good indicators of pulpal inflammation, with a new biomarker, presepsin, and to evaluate the impact of biomarker levels along with the pulp capping agents used in the treatment on the one-year success of pulpotomy treatment. Methods The study included 120 primary second molar teeth with pulpotomy indications from 75 children. To determine the pulpal inflammation status, pulpal bleeding samples were taken during treatment, and the levels of IL-6, IL-8, and presepsin were measured. During the pulpotomy treatment, MTA, NeoMTA™, and Biodentine™, and ZOE were randomly applied to groups of thirty teeth each. Patients were monitored for a period of 12 months post-treatment. Results IL-8, IL-6, and presepsin levels were significantly higher in teeth with pathology (p < 0.001). Biomarker levels were found to be higher in the NeoMTA and Biodentine groups, but this did not result in a statistically significant difference. (p > 0.05) Following pulpotomy treatment, the most successful material groups in order were MTA, ZOE, NeoMTA™, and Biodentine™. Conclusion Presepsin may be a usable indicator in predicting the level of inflammation. At the end of the one-year follow-up of pulpotomy treatment, more pathology was observed in the NeoMTA and Biodentine groups, where biomarker levels were higher, while no pathology was found in the MTA group, where biomarker levels were lower. Trial registration NCT06398327/ 20,240,503.